PENGATURAN MEREK NON-TRADISIONAL (COMPARATIVE STUDY INDONESIA DENGAN JEPANG) - Muhammad Rifqi, - (2019)
Bilateral cooperation between the Indonesian state and Japan in the field of intellectual property began in 1994 until now. As a result of the increasinly creative development of world business, brands have not only become a differentiating power for a product or service, but also have beccome a special attraction for businesses to create unusual signs for their products and services called Non-Traditional Trademarks. The cooperation has a positive impact between the two countries, especially in the regulation of Non-Traditional Trademarks, which later in Indnesia has expanded the definition of the Trademarks into Law No. 20 of 2016 concerning Trademarks and Geographical Indications.The methodology of this research is a normative jurudical research by comparing NonTraditional Trademarks arrangements found in Indonesia and Japan. This study aims to compare the Non-Traditional Trademarks arrangements in the Trademarks Law of the two countries in order to create a legal reform in Indonesia. The result is that Indonesia has only recognized 3 Non-Traditional Trademarks while Japan has protected 6 Non-Tradditional Trademarks and is likely to increase along with the times. Facts in the field the Author sees Indonesia experiencing many shortcomings ranging from infrastructure to experts to Non-Traditional Trademarks so that it requires a lot of references from other countries